Source, structural characteristics and ecological indication of dissolved organic matter extracted from sediments in the primary tributaries of the Dagu River. (February 2020) - Dong, Yanru; Li, Yue; Kong, Fanlong; Zhang, Junlong; Xi, Min
Graphical abstract: Highlights: Relative source contributions of allochthonous DOM were evaluated by stable isotope. DOM characteristics have an indicative effect on trophic status of the watershed. The humification degree of DOM increases gradually with deposition depth. It's the first study to identify release risk of heavy metal based on DOM structure. Abstract: This study aims to analyze the sources, structural characteristics of dissolved organic matter in sediments and potential ecological risk (heavy metal, nitrogen and phosphorus) based on the different characteristics of typical tributaries of the Dagu River. Carbon stable isotope is applied to calculate the relative contribution of dissolved organic matter sources in sediments of each tributary. Ultraviolet–Visible spectrophotometry and three-dimensional fluorescence spectroscopy are used to study the contents and structural characteristics of dissolved organic matter in sediments; and the potential ecological risks of nitrogen, phosphorus and heavy metals are also evaluated. The results indicate that the relative contribution of industry and rural area have high proportions in Yunxi River; Taoyuan River is dominated by forest and aquaculture pond; and industry is the main source of dissolved organic matter in the South Jiaolai River. The humification degree of dissolved organic matter in each tributary increases from surface sediment to bottom sediment. The potential risk of eutrophication decreases with the increase of depth because humic-like substances hinder the release of excessive nutrients. In addition, Yunxi River has the highest potential ecological risk of heavy metals, followed by the South Jiaolai River and Taoyuan River. This study provides a theoretical basis for ecological indication of dissolved organic matter in sediments of the Dagu River, and the spatial distribution of heavy metal risk in the study area for risk management.